Recounting Huronia Faithfully: Attenuating Our Methodology to the "Fabulation" of Truths-Telling. (June 2018) - davis halifax, nancy viva; Fancy, David; Rinaldi, Jen; Rossiter, Kate; Tigchelaar, Alex
If telling the truth is considered vital to research methodology, what happens in methodological spaces where "telling the truth" is futile? In this article, we examine the limitations, possibility, and even desirability of normative forms of empirically verifiable truth-telling and the potentialities for storied or fabulated truths with regard to knowledges that have historically been dismissed by their audiences as unreliable and even deceptive. To do so, we draw from critical theory, and Deleuzian theory in particular, to offer a detailed theoretical framework for understanding the notion of fabulated truth . We then turn to our own research to describe a project that embraced the potential of fabulation as a deeply generative methodological practice in regard to better understanding experiences of trauma. This project, which involved working alongside people with intellectual disabilities who have survived institutional incarceration, used fluid arts-based methods to help engage the affective force of trauma to story multiple truths about an otherwise unspeakable history.